MOBILISASI PROGRESIF TERHADAP PERUBAHAN TEKANAN DARAH PASIEN DI INTENSIVE CARE UNIT (ICU) - Ainnur Rahmanti; Dyah Kartika Putri (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2016)
Patient with critical condition had high morbidity and mortality rate. This condition is worsened by long term immobilization. Instability vital sign made nurses stationed delayed mobilization activities in ICU. Progressive mobilization must be started for ICU patient to decrease respiratory function, level of awareness and cardiovascular function. The objective of this study was to identify progressive mobilization activities on blood pressure parameters among critical patients in ICU. The design of this study was quai experiment design. Thirty respondents were included to the study using concequtive sampling. Progressive mobilization was given with head of bed 300 (HOB 300), head of bed450 (HOB 450) with passive range of motion, continued with right and left lateral position. Anova repeated measurement was used to identify mean difference each of blood pressure. The result of this study show there is two moment sistolic change between HOB 300 to HOB 450 and HOB 450 to right lateral position (3,3%). There is nine moment diastolic change between HOB 450 to right lateral position (16,7%). Keywords: blood pressure, ICU, Progressive mobilization